Informal Justice: An Examination of Why Ontarians Do Not Seek Legal Advice - Dylag, Matthew (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2018)
Modern access to justice scholarship takes as its premise that the focus of legal reform must be on the legal problems experienced in the day-to-day lives of the public; not just those problems that are brought before the formal court system for adjudication. In 2014, the Canadian Forum on Civil Justice [CFCJ] completed a comprehensive survey for the Cost of Justice Project inquiring into the civil legal needs among ordinary Canadians. One of the many conclusions that can be drawn from the survey data is the finding that most Ontarians do not go to lawyers in order to resolve their legal problems. Ontarians, rather, tend to engage in methods of resolution that can be categorized as informal self-help methods. This paper explores possible reasons why Ontarians do not seek out formal legal advice when they experience a legal problem. It examines various factors that may influence Ontarians’ decision not to seek formal legal advice including the respondents’ income level, their perception of the law and the category of legal problem experienced. The paper concludes that most Ontarians seek to resolve their legal problems through informal self-help methods, not because of their inability to afford legal services, but rather because of how legal problems are perceived. This work will provide insight into why most legal problems do not end up before the formal legal system, which will be of significance to policy makers who desire to make meaningful and inclusive reforms to the justice system.